2023
DOI: 10.3389/fmicb.2022.1013617
|View full text |Cite|
|
Sign up to set email alerts
|

Pathogenic ecological characteristics of PCV2 in large-scale pig farms in China affected by African swine fever in the surroundings from 2018 to 2021

Abstract: Porcine circovirus type 2 (PCV2) has been identified as the causal agent of postweaning multisystemic wasting syndrome (PMWS), an economically important multifactorial disease of the swine industry worldwide. This research designed a dual nested polymerase chain reaction (PCR) detection method to simultaneously monitor porcine circovirus type 2 (PCV2) and PCV3. The limit of detection (LoD) of sensitivity for PCV2 and PCV3 was ten copies/mL for both viruses. There was no cross-reaction with any other porcine pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…The expansion of intensive pig farms and the migration of diverse pig herds across China in recent years have necessitated the development of more effective prevention and control strategies for PCV2. This study found that PCV2 has spread widely in intensive pig farms, with a higher positivity rate observed in fattening farms, corroborating the findings of Liu et al (10) and Li et al (14). However, the positivity rates of PCV2 in breeding and fattening farms differ between Northern and Southern China (Table 2).…”
Section: Discussionsupporting
confidence: 89%
“…The expansion of intensive pig farms and the migration of diverse pig herds across China in recent years have necessitated the development of more effective prevention and control strategies for PCV2. This study found that PCV2 has spread widely in intensive pig farms, with a higher positivity rate observed in fattening farms, corroborating the findings of Liu et al (10) and Li et al (14). However, the positivity rates of PCV2 in breeding and fattening farms differ between Northern and Southern China (Table 2).…”
Section: Discussionsupporting
confidence: 89%
“…To date, the effect of this conservation effort has not been investigated based on molecular markers. Additionally, the population structure of these indigenous pig breeds has suffered tremendous shocks from African swine fever since 2018 [ 4 ]. Therefore, for better conservation of these genetic resources, population genetic analysis of the existing Hainan pig breeds is necessary.…”
Section: Introductionmentioning
confidence: 99%